GENDER, STEREOTYPES, AND WOMEN’S POTENTIAL IN LOUISA MAY ALCOTT’S LITTLE WOMEN (2019) - Purwarno, Purwarno; Amelia, Nurul; Paradiba, Adilla; Pebriani, Dela; Tanjung, Dinda; Anjani, Juli (Universitas Muhammadiyah Lampung, 2025)
This research examines gender stereotypes, and the roles and positions of women in Louisa May Alcott's Little Women. The analysis utilizes a descriptive qualitative approach, presenting and describing the data and findings in narrative form. The theoretical framework is grounded in Rosenstand's (2021) feminism, which advocates for equal opportunities and pay for women and men, free from gender-based discrimination. The research findings reveal four types of feminism depicted in the Little Women, focusing on the characters' choices between achieving their dreams and living within the confines of marriage. Little Women not only chronicles the characters' journeys from adolescence to adulthood but also illustrates their encounters with gender stereotypes embedded in societal and cultural constructs. The conclusion underscores the marginalized position of women, who lack the same opportunities as men. Various societal constraints limit women's freedoms, placing them in restrictive social roles and causing internal conflicts between pursuing personal desires and adhering to societal expectations.